PFM.16 Third trimester amniocentesis for inherited bleeding disorders can be used to inform delivery management for at risk male fetuses. (9th June 2014) - Simcox, LE; Tower, C; Byrd, L; Sempasa, B; Sutherland, M; Hay, C; Nash, M; Thachil, J; Cumming, A; Hay, E; Hobson, M; Keeney, S
Abstract : Haemophilia A and B can cause significant bleeding in affected males. Labour management of a potentially affected male should be cautious due to the potential risk of fetal haemorrhage, with delivery advised in a specialist Haemophilia centre. Historically, first trimester invasive testing has been offered but is now rarely pursued due to improved treatments. Some centres offer late (34+ weeks) gestation amniocentesis to aid delivery planning as an unaffected male can then be managed without specialist intervention. This procedure is associated with an estimated pre-term labour risk of 1% and is potentially subject to technical limitations. We report a single centre experience, over a 2 year period, of late amniocentesis in the management of 10 known haemophilia carrier females with male fetuses by first trimester fetal sexing. 50 mL of amniotic fluid was drawn at 34+ weeks gestation. 6 fetuses were confirmed as affected, 2 unaffected and in 2 cases no result was obtained, relating to quality of sample and the underlying mutation. One carrier whose fetus was unaffected subsequently delivered in her local obstetric unit. Gestation at delivery ranged from 36–41 weeks with a median gestation of 38 weeks. Late amniocentesis yields a result in 80% of cases and can be used to guide delivery management where the haemophilia mutation is known. In our series, no result could be provided in 2 out of 3 cases associated with the severe haemophilia A intron 22 inversion mutation. Each diagnostic episode requires specific counselling regarding potential limitations of the technique.